The use of video in standardized patient training to improve portrayal accuracy: A randomized post-test control group study. (3rd August 2015) - Schlegel, Claudia; Bonvin, Raphael; Rethans, Jan Joost; van der Vleuten, Cees
Abstract: Introduction : High-stake objective structured clinical examinations (OSCEs) with standardized patients (SPs) should offer the same conditions to all candidates throughout the exam. SP performance should therefore be as close to the original role script as possible during all encounters. In this study, we examined the impact of video in SP training on SPs' role accuracy, investigating how the use of different types of video during SP training improves the accuracy of SP portrayal. Methods : In a randomized post-test, control group design three groups of 12 SPs each with different types of video training and one control group of 12 SPs without video use in SP training were compared. The three intervention groups used role-modeling video, performance-feedback video, or a combination of both. Each SP from each group had four students encounter. Two blinded faculty members rated the 192 video-recorded encounters, using a case-specific rating instrument to assess SPs' role accuracy. Results : SPs trained by video showed significantly ( p  < 0.001) better role accuracy than SPs trained without video over the four sequential portrayals. There was no difference between the three types of video training. Discussion : Use of video during SP training enhances the accuracy of SP portrayal compared with no video, regardless of the type of video intervention used.